In vitro ovarian follicle growth: a comprehensive analysis of key protocol variables. Issue 3 (14th May 2020) - Simon, Leah E; Kumar, T Rajendra; Duncan, Francesca E
Abstract: Folliculogenesis is a complex process that requires integration of autocrine, paracrine, and endocrine factors together with tightly regulated interactions between granulosa cells and oocytes for the growth and survival of healthy follicles . Culture of ovarian follicles is a powerful approach for investigating folliculogenesis and oogenesis in a tightly controlled environment. This method has not only enabled unprecedented insight into the fundamental biology of follicle development but also has far-reaching translational applications, including in fertility preservation for women whose ovarian follicles may be damaged by disease or its treatment or in wildlife conservation. Two- and three-dimensional follicle culture systems have been developed and are rapidly evolving. It is clear from a review of the literature on isolated follicle culture methods published over the past two decades (1980–2018) that protocols vary with respect to species examined, follicle isolation methods, culture techniques, culture media and nutrient and hormone supplementation, and experimental endpoints. Here we review the heterogeneity among these major variables of follicle culture protocols. Abstract : Follicle culture is a widespread technique used in reproductive biology, and significant heterogeneity exists in protocols, including species examined, isolation methods, culture techniques, media and hormone supplementation, and experimental end points.